Experiences of young girls and women undergoing ovarian tissue cryopreservation: a systematic review and thematic synthesis. (2nd October 2022) - Khattak, Hajra; Woodman, Hannah; Afifi, Yousri; Amorim, Christiani A.; Fishel, Simon; Gallos, Ioannis; Coomarasamy, Arri; Topping, Annie
Abstract: The aim of this study was to explore the experiences of young girls and women who underwent or considered ovarian tissue cryopreservation (OTC) using a systematic review of qualitative studies with thematic synthesis framework. Major electronic databases: MEDLINE, EMBASE, the Cochrane Library, CINAHL and PsycINFO were searched from 1946 to May 2020 and reference lists of relevant articles were hand searched. Any studies that described a qualitative inquiry and highlighted the experiences of women with regards to OTC were included. Two independent reviewers screened the title and abstracts and made a selection against inclusion criteria. Main outcomes measures were experiences of women who have considered and/or undergone OTC, decision making in women who underwent or considered OTC and patient education. Nineteen studies were assessed for full text eligibility and four were included in analysis. 144 verbatim quotations from 85 participants in high income countries (UK, USA and Denmark) were included. Two studies adopted grounded theory approach, one phenomenology and one inductive content analysis. Four themes were generated; participants described their experiences as emotional, involving complex decision-making, helping them prepare for the long-term consequences of potentially losing their fertility and hormonal function, as well as their experience being educational. Additionally, the more practical aspects of the procedure such as OTC being invasive as well as costs implications were highlighted. Women and young girls are often involved in making time-sensitive decisions whether or not to undergo OTC. Healthcare professionals involved in the care of young girls and women undergoing this method need to also take into consideration the emotional wellbeing of the patients as well as the time and expertise it requires to help them make an informed decision.